Deep groundwater irrigation altered microbial community and increased anammox and methane oxidation in paddy wetlands of Sanjiang Plain, China - Li, Huai; Song, Aiwen; Qiu, Ling; Liang, Shen; Chi, Zifang (Frontiers in Microbiology, 2024)
The over-utilizing of nitrogen fertilizers in paddy wetlands potentially threatens to the surrounding waterbody, and a deep understanding of the community and function of microorganisms is crucial for paddy non-point source pollution control. In this study, top soil samples (0–15 cm) of paddy wetlands under groundwater's irrigation at different depths (H1: 6.8 m, H2: 13.7 m, H3: 14.8 m, H4: 15.6 m, H5: 17.0 m, and H6: 17.8 m) were collected to investigate microbial community and function differences and their interrelation with soil properties. Results suggested some soil factor differences for groundwater's irrigation at different depths. Deep-groundwater's irrigation (H2-H6) was beneficial to the accumulation of various electron acceptors. Nitrifying-bacteria Ellin6067 had high abundance under deep groundwater irrigation, which was consistent with its diverse metabolic capacity. Meanwhile, denitrifying bacteria had diverse distribution patterns. Iron-reducing bacteria Geobacter was abundant in H1, and Anaeromyxobacter was abundant under deep groundwater irrigation; both species could participate in Fe-anammox. Furthermore, Geobacter could perform dissimilatory nitrate reduction to ammonia using divalent iron and provide substrate supply for anammox. Intrasporangium and norank_f_Gemmatimonadacea had good chromium- and vanadium-reducting potentials and could promote the occurrence of anammox. Low abundances of methanotrophs Methylocystis and norank_f_Methyloligellaceae were associated with the relatively anoxic environment of paddy wetlands, and the presence of aerobic methane oxidation was favorable for in-situ methane abatement. Moisture, pH, and TP had crucial effects on microbial community under phylum- and genus-levels. Microorganisms under shallow groundwater irrigation were highly sensitive to environmental changes, and Fe-anammox, nitrification, and methane oxidation were favorable under deep groundwater irrigation. This study highlights the importance of comprehensively revealing the microbial community and function of paddy wetlands under groundwater's irrigation and reveals the underlying function of indigenous microorganisms in agricultural non-point pollution control and greenhouse gas abatement.